Técnica alternativa de conformação de junção a partir de tubos metálicos - Foli, Cristiano Roberto Martins; Menezes, Miguel Ângeld; Moreira Filho, Lindolfo Araújo [UNESP] (My University, 2003)
This work presents a technique for the cold forming of thin-walled cylindrical tubes, aimed at obtaining a symmetrical joint with an unconventional forming technique, using elastomer rod. The purpose of this work is to investigate the influence of the anisotropy on the total forming force, through the use of elastomer for obtaining T-junctions, in order to get a better result between experimental values and the analytical solution. For total forming force forecasting, it will be used the upper-bound theory and for a better understanding on the anisotropy behavior of the material, it will be employed the quadratic yielding criterion proposed by Hill. The employed materials for such investigation were Aluminum, Brass and Copper.
Alternative technique of forming of junction on metal tubes
Keywords: Anisotropy; Elastomer rod; Forming; Elastomer rods; Junctions; Elastomers; Tubes (components); Metal forming